The Problems Facing the Second Semester Students in the English Department in Learning English Modal Verbs - Saad Elarfi , Ms.Nora (مجلة كلية الاداب, 2022)
The present study is mainly concerned with a very important area of English grammar which is “The English Modal Verbs” in terms of the technique of introducing them to second semester students in the English department at the university of Benghazi. The researcher tries to clarify the problems that our students face in learning the English Modal Verbs because of introducing them individually, not as members of three basic types of modality which are Epistemic Modality, Deontic Modality, and Dynamic Modality. The population of the study consisted of ten teachers and thirty students.. The main purpose of this study is to discover the difficulties that our students face in learning these modal verbs which have so many different meanings that make it difficult to learn. Three tools of investigation were used, namely a questionnaire for the sample teachers and a test for the sample students. The analysis of the collected data has shown that both of the sample teachers and the sample students face difficulty. As for students, they face difficulty in dealing with the English Modal Verbs when they come in a context while they could master them in individual sentences. That is because of the way which is used in their textbook in dealing with each Modal Verb individually.